Usage Status and Regional Variations of Acupotomy in a Korean Medicine Clinic: A Single-Center, Retrospective Analysis of Medical Records - Kyungho Kang; Jihyeon Hwang; Hongmin Chu; Young-ung Lee; Hyocheong Chae; Jeong-youn Lee; Kwanghwan Lim; Sehun Jung; Seongjun Park; Seong-Hun Choi; Ju hyeon Mun; Jaehyo Kim; et al. (MEDrang Inc., 2022)
Background Acupotomy is a type of acupuncture where a scalpel-shaped needle (miniscalpel needle) is used instead of a normal acupuncture needle to exfoliate adhesion sites or to relax entrapped regions. This study aimed to identify the descriptive characteristics of patients who received acupotomy treatment at a single Korean Medicine Clinic. Methods This retrospective review analyzed the medical charts of patients who had received acupotomy at least once from August 2017 to December 2019 at a single Korean Medicine Clinic. The demographic characteristics, chief complaints, acupotomy treatment sites, and principal diagnosis codes were analyzed. Results We identified 551 outpatients; the average age was 52 ± 14.26 years and 49.9% were male. The patients underwent an average of 8.47 sessions of acupotomy. Altogether, 35.91% of the acupotomy treatments were administered to the spinal regions, of which 60.01% were in the lumbar region. The codes related to the lumbar spinal condition/disease which were used most frequently. The chief complaints were dizziness, lumbar spinal stenosis, and Dupuytren's contracture in patients over 60 years of age. Conclusions This is the 1st analysis of acupotomy treatment patterns in Korea to date. Acupotomy is primarily administered in the treatment of spinal conditions/diseases, especially for those involving the lumbar region. Future studies are necessary to determine the clinical outcomes of patients who receive acupotomy treatment and the safety of this treatment.